PENGARUH KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (Studi Kasus Perusahaan Manufaktur di BEI Tahun 2015-2017) - Yohanis Emass Cristofer; Paskah Ika Nugroho (Universitas Pandanaran, 2019)
This research aims to review the influence of managerial ownership on the value a company with the size of thecompany as variable moderation. The collection of data using a method of pusposive sampling at manufacturingcompanies listed on BEI in observation 2015-2017. Sample data obtained as much as 47 company that inaccordance with the research criteria. The measurement of the dependent variable using PER (price to earningratio), variable independent is using managerial ownership, and moderating variable using total assets. Dataanalysis techniques in this study is using multiple linear regression analysis. Testing on this study using an appSPSS version 22. The results of this research stated that ownership of managerial no significant impact on thevalue of the company and the size of the corporations cannot moderating influence of managerial ownership onthe company value.Keywords: managerial ownership, managerial ownership the company, the size of the company